Teaching Gender in the History Classroom: An Investigation into the Initial Training of Primary Education Teachers - Delfín Ortega-Sánchez (MDPI AG, 2019)
In this article, we aim to, firstly, examine the social representations of a group of trainee Primary-Education teachers (n = 62) with regard to both the procedures and the social purposes of teaching History at school and, particularly, the role of women in History lessons. Secondly, we attempt to intervene in those representations and to evaluate the potential impact of a teacher training programme both in and for education in gender equality. Empirically, we employ a quantitative (means and standard deviations) and inferential (Wilcoxon’s signed-rank and Kendall’s tau-b tests) pre-experimental, pre-test/post-test design with no control group. The results shed light on the generalised acceptance of critical curricular focuses in History lessons that are directed towards training in historical and social thinking skills from a gender perspective. The sex of prospective teachers does not seem to influence these results. Likewise, these results confirm the didactic potential of using critical literacy resources in the classroom for improving the visibility of women and the female experience in the historic−social discourse of History as it is taught and in the promotion of models of global citizenship.